2019
DOI: 10.1021/acsami.8b21903
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of Phosphorus Species on Graphene with a Stabilized Electrochemical Interface

Abstract: Phosphorus doping is an effective approach to tailor the surface chemistry of carbon materials. In this work, two-dimensional graphene, as a simplified model for all sp 2 hybrid carbon allotropes, is employed to explore the surface chemistry of P-doped carbon materials. Thermally reduced graphene oxide, with abundant residual oxygen functionalities, is doped by phosphorus heteroatoms through H 3 PO 4 activation, followed by passivation in an inert atmosphere. The structural evolution of the phosphorus species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 55 publications
(108 reference statements)
5
74
0
Order By: Relevance
“…The plots of the frequency dependence of the total capacitance, real capacitance C′ and imaginary capacitance C′′ are shown in Figure S9 d–f of the Supporting Information. Similar to the results of the GCD curve, ACNF‐12 has higher specific capacitance than ACNF‐6 and ACNF‐18 . The relationship between the total impedance and frequency for the ACNFs is shown in Figure 4 g. The total impedance of ACNF‐12 is lower than those of ACNF‐6 and ACNF‐18.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The plots of the frequency dependence of the total capacitance, real capacitance C′ and imaginary capacitance C′′ are shown in Figure S9 d–f of the Supporting Information. Similar to the results of the GCD curve, ACNF‐12 has higher specific capacitance than ACNF‐6 and ACNF‐18 . The relationship between the total impedance and frequency for the ACNFs is shown in Figure 4 g. The total impedance of ACNF‐12 is lower than those of ACNF‐6 and ACNF‐18.…”
Section: Resultssupporting
confidence: 74%
“…Similart ot he results of the GCD curve, ACNF-12 has highers pecific capacitance than ACNF-6 and ACNF-18. [49] The relationship between the total impedance and frequency for the ACNFs is shown in Figure 4g .T he total impedance of ACNF-12i sl ower than those of ACNF-6 and ACNF-18. This indicates that ACNF-12 has al ow internal resistance.…”
Section: Resultsmentioning
confidence: 97%
“…Three major peaks split from high-resolution P2p peaks at 132.3, 133.1, and 134.0 eV were accordingly attributed to the C 3 −PO, C−P−O, and C−O−P groups (Figure 2b). [25,26] Whereas, the C−P species at about 130.2 eV unexpectedly absented from these five prepared samples. For three P species contents, from Table 1, it could be found that the C−O−P contents in five samples first increased and then decreased with the increase of heating temperature while the contents of C 3 −PO and C−P−O groups kept decreasing, indicating that the C−O−P group is more stable than the other two P moieties.…”
Section: Structure Characterizationmentioning
confidence: 86%
“…[ 1–4 ] Carbon materials have shown tremendous potential and advantages in the field of SCs due to the excellent surface chemical property, good conductivity, adjustable pore structure, and high specific surface area. [ 5–11 ] Generally, the processes for synthesizing carbon materials include freeze‐drying, [ 12 ] acid pickling, [ 13 ] template method, [ 14 ] or organic reaction, [ 15 ] which are complex and time‐consuming tasks. On the other hand, surface modification is proved to improve the electrochemical performance of electrode materials efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, P is larger and stronger than N due to atomic radius and electron donor capacity. [ 11 ] More importantly, P as an oxidation protective agent can be helpful to improve the cyclic stability, capacity retention, and working voltage window of capacitors. [ 18 ] In addition, O‐doped microporous carbon has been proved to improve the hydrophilicity of the surface to aqueous electrolytes, which can facilitate the redox reaction and ensure excellent rate performance.…”
Section: Introductionmentioning
confidence: 99%